Issues in hostile take-overs in the financial sector - Russell, Patsy ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Reviews the main issues in mergers and acquistions in the financial sector. Insicates that within the region, the greater percentage of mergers have occured largely through government initiative.